Limited Fronto-Temporo- Parietal Craniectomy in Traumatic Brain Injury: My Experience - Sharma, Krishna (Nepal Journal of Neuroscience, 2016)
Amidst the uncertainty of benefit of decompressive craniectomy (DC) in severe traumatic brain injury (TBI), the procedure is still widely performed as a life saving attempt. Different types of DC have been described. A timely performed limited fronto-temporoparietal (FTP) decompression is found to be adequate enough to reduce the intracranial pressure (ICP) quickly and sufficiently, preventing medial temporal herniation. This can be further augmented by an adequate, liberal and watertight duroplasty to accommodate the swollen injured brain, which can be achieved by using patients’ own tissues like thickened subcutaneous areolar tissue and temporalis fascia. DC is usually considered as a two-step surgery where decompression is done in the first step and cranioplasty in the second. It can be made a single step surgery by replacing the bone in small pieces extradurally during the primary surgery itself, to avoid second surgery (cranioplasty). The details of the procedure and its results have been described and review of related literature has been done. Nepal Journal of Neuroscience 12:8-13, 2015